Shared pedigree relationships and transmission of unreduced gametes in cultivated banana - Martin, Guillaume; Baurens, Franc-Christophe; Labadie, Karine; Hervouet, Catherine; Salmon, Frédéric; Marius, Franck; Paulo-de-la-Reberdiere, Nilda; Van Den Houwe, Ines; Aury, Jean-Marc; D’Hont, Angélique; Yahiaoui, Nabila (Oxford University Press, 2023)
Abstract Background and Aims Cultivated bananas resulted from inter(sub)specific hybridizations involving Musa species and subspecies (M. acuminata subspecies, M. schizocarpa, M. balbisiana) and the subsequent selection, centuries ago, of hybrids with parthenocarpic, seedless fruits. Cultivars have low fertility and are vegetatively propagated, forming groups of somaclones. Relatively few of them, mainly triploids, are grown on a large scale and characterization of their parental relationships may be useful for breeding strategies. Here we investigate parental relationships and gamete-type contributions among diploid and polyploid banana cultivars. Methods We used SNP genotyping data from whole-genome sequencing of 178 banana individuals, including 111 cultivars, 55 wild bananas and 12 synthetic F1 hybrids. We analysed the proportion of SNP sites in accordance with direct parentage with a global statistic and along chromosomes for selected individuals. Key Results We characterized parentage relationships for 7 diploid cultivars, 11 triploid cultivars and 1 tetraploid cultivar. Results showed that both diploid and triploid cultivars could have contributed gametes to other banana cultivars. Diploids may have contributed 1x or 2x gametes and triploids 1x to 3x gametes. The Mchare diploid cultivar group, nowadays only found in East Africa, was found as parent of two diploid and eight triploid cultivars. In five of its identified triploid offspring, corresponding to main export or locally popular dessert bananas, Mchare contributed a 2x gamete with full genome restitution without recombination. Analyses of remaining haplotypes in these Mchare offspring suggested ancestral pedigree relationships between different interspecific banana cultivars. Conclusions The current cultivated banana resulted from different pathways of formation, with implication of recombined or un-recombined unreduced gametes produced by diploid or triploid cultivars. Identification of dessert banana’s parents and the types of gametes they contributed should support the design of breeding strategies.